Lnc90386 Sponges miR-33-5p to Mediate Mycoplasma gallisepticum-Induced Inflammation and Apoptosis in Chickens via the JNK Pathway - Sun, Yingfei; Wang, Yingjie; Zou, Mengyun; Wang, Tengfei; Wang, Lulu; Peng, Xiuli (Frontiers in Immunology, 2022)
Mycoplasma gallisepticum (MG) is one of the most important pathogens that cause chronic respiratory disease (CRD) in chickens. Recently, long noncoding RNAs (lncRNAs) have been discovered as new regulators for many diseases and some lncRNAs could function as competing endogenous RNAs (ceRNAs) to regulate mRNAs by competitively binding to miRNAs. Here, the expression of miR-33-5p was up-regulated in MG-infected chicken embryonic lungs and chicken embryo fibroblast cells (DF-1), and Lnc90386 negatively correlated with miR-33-5p. miR-33-5p as a new regulator for MG infection by targeting JNK1 to repress apoptosis, inflammatory factors, and an adhesion protein of MG-HS (pMGA1.2) expression in DF-1 cells. Further analyses showed that Lnc90386 sponged miR-33-5p to weaken its silencing of JNK1, forming the ceRNA regulatory network. Furthermore, knockdown of Lnc90386 significantly inhibited apoptosis, inflammatory factors and promoted proliferation of DF-1 cells, co-treatment of miR-33-5p inhibitor and Lnc90386 knockdown showed that knockdown of Lnc90386 partially eliminated the effect of the miR-33-5p inhibitor on inflammation, cell apoptosis and proliferation. In conclusion, miR-33-5p inhibits JNK signaling pathway via targeting JNK1 to defend against MG infection, and is regulated by Lnc90386.